2020
DOI: 10.7759/cureus.8304
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Acromial Anatomy and Rotator Cuff Tears in Saudi Arabian Population

Abstract: Objectives We investigated the relationship between acromial shape, classified as Type I-IV by magnetic resonance imaging, and the occurrence and characteristics of rotator cuff tears (RCTs). Methods This retrospective cohort study included 89 patients aged 25-60 years who underwent RCT surgeries in the Orthopedic Department at King Abdulaziz University Hospital (KAUH) from January 2014 to April 2019. We collected imaging findings from the KAUH record system, which were then entered into a Google form (Google,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In terms of left or right shoulder, a statistically significant correlation was not found (p<0.065) in this study. This has been evaluated as compatible with the literature [5,15,21]. When evaluated in terms of subacromial distance, Polatet al [11] showed that there was no significant difference between male and female patients and right and left shoulders (p=0.309, p=0.454, respectively).…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…In terms of left or right shoulder, a statistically significant correlation was not found (p<0.065) in this study. This has been evaluated as compatible with the literature [5,15,21]. When evaluated in terms of subacromial distance, Polatet al [11] showed that there was no significant difference between male and female patients and right and left shoulders (p=0.309, p=0.454, respectively).…”
Section: Discussionmentioning
confidence: 59%
“…An association was found between RCTs and females (p<0.001). When the RCTs were evaluated, it was determined to male 182 (37%) and females 310 (67%), which differs from previous publications [5,15,21]. We think that this is because our females are more delicate as stated in the literature [7,12].…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…They also argued that changes such as bone spur within the acromion develop over time as a result of RCT rather than the cause of RCT. Unlike many studies, Almokhtar et al (16) found that a flat acromion is the most frequently seen type among all patients with RCTs.…”
Section: Discussionmentioning
confidence: 88%